To Treat or Not to Treat: The Role of Adjuvant Radioiodine Therapy in Thyroid Cancer Patients. (1st November 2012) - Carballo, Marilee; Quiros, Roderick M.
Abstract : Radioactive iodine (RAI) is used in treatment of patients with differentiated papillary and follicular thyroid cancer. It is typically used after thyroidectomy, both as a means of imaging to detect residual thyroid tissue or metastatic disease, as well as a means of treatment by ablation if such tissue is found. In this paper, we discuss the indications for and the mechanisms of RAI in the treatment of patients with thyroid cancer. We discuss the attendant risks and benefits that come with its use, as well as techniques used to optimize its effectiveness as an imaging tool and a therapeutic modality.